1933
DOI: 10.1017/s0007485300035501
|View full text |Cite
|
Sign up to set email alerts
|

The Synonymy and Distribution ofChrysomyia rufifacies(Macq.), an Australian Sheep Blowfly

Abstract: The Australian sheep “ blowfly ” Chrysomyia rufifacies, Macq., is shown by a study of chaetotaxy and the genitalia to be distinct from C. albiceps with which it has been considered identical. A discussion is given of the composite genus Chrysomyia and the genera into which Séguy has recently divided it. The synonymy of C. rufifacies is given and also the distribution of C. rufifacies, C. albiceps and C. putoria, the three species which Patton has considered synonymous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

1963
1963
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 10 publications
4
23
0
Order By: Relevance
“…After examination of our specimens, we corroborate the original descriptions of Holdaway (1933), wherein C. albiceps and C. putoria present a dark brown colour on flagellomere I, and C. rufifacies presents a pale brown colour on the inner side of the dorsal part of the antenna. Although the colours of the anatomical structures of insects may present a high level of variation depending on their preservation conditions, we are confident in highlighting this character to aid in the diagnosis of C. rufifacies due to the varying conditions of preservation exhibited by the specimens we examined.…”
Section: Third Antennal Segment: (0) Dark Brown Versus (1) Inner Facesupporting
confidence: 87%
See 4 more Smart Citations
“…After examination of our specimens, we corroborate the original descriptions of Holdaway (1933), wherein C. albiceps and C. putoria present a dark brown colour on flagellomere I, and C. rufifacies presents a pale brown colour on the inner side of the dorsal part of the antenna. Although the colours of the anatomical structures of insects may present a high level of variation depending on their preservation conditions, we are confident in highlighting this character to aid in the diagnosis of C. rufifacies due to the varying conditions of preservation exhibited by the specimens we examined.…”
Section: Third Antennal Segment: (0) Dark Brown Versus (1) Inner Facesupporting
confidence: 87%
“…All collected flies were taken to the lab for identification by taxonomic keys (Holdaway, 1933;Guimarães et al, 1978;Dear, 1985;Guimarães and Papavero, 1999) and comparison with identified vouchers.…”
Section: Obtaining Samples For Analysismentioning
confidence: 99%
See 3 more Smart Citations